Development of a Visual Interface of Glucose Metabolism Based on Compartment Mathematical Models - Olay-Blanco, A. A.; Quiroz-Compeán, G. (Revista Mexicana de Ingenieria Biomedica, 2017)
Diabetes is a pandemic disease whose incident rate has been rising in the last decades. Therefore, it is important to propose strategies for its diagnosis, treatment and monitoring. One of the recent approaches on diabetes treatment is the continuous monitoring, which provides enough information about the metabolic state of the patient throu-ghout the day. This information can be used to simulate virtual patients which are useful tools in treatment strate-gies. Thus, the objective of this research is to propose a visual interface to simulate virtual patients, this is based on compartmental mathematical models considering changes in metabolic parameters and treatment modifications. The interface was made in MATLAB® and simulates three kinds of patients (healthy, type I diabetic, type II diabetic). The results show an interface that presents the functionality of the mathematical models in an illustrative way and it allows the visualization of the metabolic state of the patient; as well as the medication usage and meal intake. A li-mitation of this approach is the validation of the interface with experimental data of the three kinds of patients. Once it was validated, this tool could contribute to the development of in silico technology to generate virtual patients.